Field-friendly MUNNG® optima simple test kit for quick qualitative assessment of iodine and iron presence in double-fortified salt - Godbole, Ujwala; Gupta, Divya; Godbole, Nachiket; Godbole, Madan (Frontiers in Nutrition, 2023)
Background Successful efficacy studies and a long-term effectiveness studies have encouraged the Indian government to provide double fortified salt (DFS) in the mid-day meal (MDM) to children. Massive up scaling of manufacturing and distribution requires robust monitoring by community and field workers for quality checks. Equipping field workers with simple testing kits (STKs) capable of qualitative detection of iron and iodine in DFS is important. As the consumer acceptance of foods is based on several factors including sensory characteristics, performance, convenience, cost, nutrition, and product image, a variety of iron compounds are in use for fortification. However, it becomes challenging to provide a kit that can overcome chemical masking of iodine detection by iron compounds. Objectives: We aimed at (1) development of a field friendly STK for quick qualitative assessment of iodine and various forms of iron present in DFS, (2) To check its validity under field conditions. Methods We put in place reagents combined using known chemical reactions and balanced use of oxidants to overcome the problems of encapsulation, and to maximize the use, by enabling reagent combination to react with all forms of iron. Results The kit reagents successfully detect iodine as well as three commonly used iron fortificants in DFS. Published field trials confirmed the specificity and sensitivity of the developed kit. The simplicity and use of kit by a field worker can be seen in enclosed video. Conclusion Successful development of this field worker friendly STL will help to monitor the micronutrient content of fortified salt.